Щодо впливу національних чинників на формування біотичної складової матеріального рюкзака підприємства - Cherevatskyi, Danylo Yu.; Bojko, Oksana V.; Smirnov, Roman G. (Institute of Industrial Economics of NAS of Ukraine, 2024)
Relevance of research. Sustainable Development Goal No. 12 refers to reducing the resource intensity of the economy by reducing the costs of material input in production chains. The famous German scientist Friedrich Schmidt-Blick proposed the concept of an ecological backpack as a characteristic of hidden material flows accompanying the entire life cycle of a product. A separate component of the backpack is the biotic part, which was heavy enough when, for example, horse traction was used in old mines. Food self-satisfaction of the staff based on the salary led to the fact that the consumption of food in the production process remained outside the analysis of the company's material flows.The purpose of the study is to prove/refute the validity of the hypothesis regarding the significant dependence of the biotic component of the material backpack on national traditions and the material income of workers of industrial enterprises.Research methods: mathematical statistics. The basis of research is long-term observation of food consumption in Ukraine and abroad, in particular, Poland and China.Main results. In the course of research, certain traditions characteristic of Ukrainian realities were revealed: consumption of food products by the average Ukrainian with a probability of 0.95 is 58.75±0.04 kg per month (698±0.5 kg per year);  the structure of the consumer basket in Ukraine contains 33% – milk and dairy products, 15% – vegetables; 14% – bakery products and cereals, 11% – potatoes, 8% – meat and meat products; the average person in Ukraine consumes more food than recommended by the Ministry of Health of Ukraine (by approximately 5%); residents of rural areas consume more food than urban residents (by almost 6% – 57.9 kg per month versus 54.7 kg).It has been statistically proven that the annual volume of food consumption by residents of Ukraine (689 kg) is significantly greater than that of residents of Poland (456 kg) and, even more so, China (413 kg). National differences concerning food preferences have been revealed. Quantitative differences in the national consumption of food products by producers determine the different content of the material backpack of industrial products, which provides certain competitive advantages/disadvantages to the subjects of international market activity.In addition to the national traditions of food consumption, there are laws that determine the influence of the average per capita household equivalent total income on the weight of the food basket.On the basis of official statistical data, a mathematical dependence of the logarithmic form of the amount of food consumption on the average per capita income of a household member is proposed.